2022
DOI: 10.3390/jcm11112968
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Clinical Characteristics, Laboratory Findings, and Outcomes of Hypoxemic and Non-Hypoxemic Patients Treated at a Makeshift COVID-19 Unit in Bangladesh: A Retrospective Chart Analysis

Abstract: Background: Starting on 31 December 2019, from Wuhan City, China, Coronavirus disease 2019 (COVID-19) caused a global pandemic by 11 March 2020. Bangladesh detected its first case on 8 March 2020, only 66 days later the detection of the first case in China. We aimed to describe the epidemiology, clinical features, laboratory characteristics, and outcomes of Bangladeshi COVID-19 patients. Methods: This retrospective chart analysis compared Bangladeshi COVID-19 patients with hypoxemia compared to those without h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…We observed in our study, deceased patients had high level of total leucocytes count, neutrophil, CRP, D-Dimer, and low lymphocyte than the survivors. A study done in similar set up in Bangladesh during COVID-19 era, the study team found that the critically ill patients had lymphopenia, high D-Dimer and CRP level than those who are not critically ill [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed in our study, deceased patients had high level of total leucocytes count, neutrophil, CRP, D-Dimer, and low lymphocyte than the survivors. A study done in similar set up in Bangladesh during COVID-19 era, the study team found that the critically ill patients had lymphopenia, high D-Dimer and CRP level than those who are not critically ill [ 39 ].…”
Section: Discussionmentioning
confidence: 99%